Thomas Merton: Catholic modernist?. Issue 9 (1st September 2020) - Feldman, Matthew
ABSTRACT: This essay takes a new look at the mid to late century monk-poet, Thomas Merton. A progressive Trappist with both Zen and Catholic convictions and a man whose life as a contemplative was offset by fame as a diarist and letter writer, Merton cuts an unusual, contradictory figure in the 1960s counterculture. I examine his works of modernist criticism and his 1941 novel, M y Argument with the Gestapo, for evidence of a consistent moral aesthetic scheme. Merton's fiction and modernist criticism invoked an ironic 'aesthetic of deadness' yet at the same promoted the spiritual dignity of individuals against what Merton saw as the stultifying uniformity of post-war secular humanism. Writing on the cusp between late modernism and postmodernism, his final decade also saw him return to modernist literature, albeit largely 'late modernists' – from so-called absurdists like William Faulkner and above all, Albert Camus, in order to develop an approach to modernist art as revelatory and premonitory of modern man's increasing spiritual impoverishment.